2003
DOI: 10.1128/aac.47.7.2342-2344.2003
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibilities ofMalasseziaSpecies to a New Triazole, Albaconazole (UR-9825), and Other Antifungal Compounds

Abstract: The in vitro activity of the new triazole albaconazole (UR-9825) in comparison with those of flucytosine, fluconazole, ketoconazole, itraconazole, and voriconazole against 70 strains of Malassezia spp. was determined by a microdilution method using a colorimetric indicator for metabolic activity. Albaconazole showed an in vitro profile similar to those of the different antifungals tested (MIC < 0.06 g/ml for all the strains).Yeasts of the genus Malassezia are part of the normal mycota of the skin of humans and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
43
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 26 publications
13
43
1
2
Order By: Relevance
“…Although terbinafine, amorolfine, and established and newer azole compounds have been tested against Malassezia skin isolates by BMD methods (4,12), data on the in vitro performance of amphotericin B are almost exclusively associated with cases of bloodstream infections (1,9,18). However, these studies were performed prior to the resolution of the taxonomic status of Malassezia species and the recognition of new species (5).…”
Section: Discussionmentioning
confidence: 99%
“…Although terbinafine, amorolfine, and established and newer azole compounds have been tested against Malassezia skin isolates by BMD methods (4,12), data on the in vitro performance of amphotericin B are almost exclusively associated with cases of bloodstream infections (1,9,18). However, these studies were performed prior to the resolution of the taxonomic status of Malassezia species and the recognition of new species (5).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with other reports, this study also found higher in vitro antifungal activity against all the tested clinical isolates of Malassezia spp, with itraconazole. [8,14,16] In this study fluconazole MICs were significantly higher than those observed for other azole drugs and ranged from ≤ 0.125 µg/mL -16µg/mL for all the isolates in PV cases. This is similar to or lower than those documented in various other studies.…”
Section: Resutsmentioning
confidence: 92%
“…The ketoconazole MICs range from ≤ 0.03 -8 μg/mL with all the species tested, These values are similar to or higher than those documented in other studies. [14,15,8,17] Garau M et al [8] registered MICs of ≤0.03µg/mL against 70 isolates of Malassezia. Gupta AK et al [15] demonstrated that out of 55 of strains of Malassezia the MIC ranges as ≤ 0.03µg/mL -0.125μg/mL with 95% of them having an MIC of ≤ 0.03μg/mL.…”
Section: Resutsmentioning
confidence: 99%
See 2 more Smart Citations